Pengaruh Kebijakan Deviden, Sales Growth, Current Ratio, Debt To Equity Ratio dan Ukuran Perusahaan Terhadap Profitabilitas Pada Perusahaan Sub Sektor Makanan dan Minuman Yang Terdaftar Pada BEI Periode 2017-2021 - novi pefbrina; Nilmadesri Rosya; Gustia Harini (CERED Indonesia Institute, 2023)
This research was conducted to analyze the effect of dividend policy, sales growth, current ratio, debt to equity ratio and company size on profitability. The population in this study are food and beverage sub-sector companies listed on the IDX for the 2017-2021 period with a sample of 17 companies taken by purposive sampling method. This study uses panel data regression analysis and shows that dividend policy has a negative and significant effect on profitability and secondly sales growth has a negative and insignificant effect on profitability and the third current ratio has a negative and insignificant effect on profitability and the fourth debt to equity ratio has a negative and insignificant effect on profitability and the fifth company size has a negative and insignificant effect on profitability and the sixth dividend policy, sales growth, current ratio, debt to equity ratio and company size affect profitability.